EFFECTIVENESS OF SCHOOL ADMINISTRATION SERVICE SYSTEM IN THE DIGITAL ERA: CASE STUDY AT SMAN 1 KREMBUNG - UB, A. Riyadh; Sukmana, Hendra; Sukmono, Rita Ambarwati (ANTIS PUBLISHER, 2024)
Objective: This study aims to analyze the effectiveness of the school administration service system at SMAN 1 Krembung in responding to the demands and challenges of the digital era. The research focuses on identifying strengths, weaknesses, and areas for development in the implementation of digital administrative practices within the school environment. Method: A mixed methods approach was utilized, combining both qualitative and quantitative techniques. Data were collected through structured interviews with administrative staff and school leaders, observations of administrative workflows, and surveys distributed to staff and stakeholders. The integration of these methods allowed for a comprehensive analysis of administrative practices and perceptions. Results: The findings reveal that SMAN 1 Krembung has begun to implement several digital technologies to support its administrative processes. However, a notable gap remains between the desired efficiency and the actual performance of the system. Key challenges include insufficient digital infrastructure, limited staff digital competencies, and a lack of system integration across different administrative units. Novelty: This study offers one of the few in-depth evaluations of school administration service systems in an Indonesian public high school context during the digital transformation era. It contributes practical recommendations for improving administrative service quality, emphasizing the importance of infrastructure upgrades, targeted staff training, and the development of an integrated administrative system to support educational management in the digital age.